2007
DOI: 10.1007/s00430-007-0055-0
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins: linking danger and pathogen recognition

Abstract: Besides their central function in protein folding and transport within the cell, heat shock proteins (HSP) have been shown to modulate innate and adaptive immune response: (1) HSP mediate uptake and MHC presentation of HSP-associated peptides by antigen-presenting cells (APC). (2) HSP function as endogenous danger signals indicating cell stress and tissue damage to the immune system. (3) HSP bind pathogen-associated molecular pattern (PAMP) molecules and modulate PAMP-induced Toll-like receptor (TLR) signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 66 publications
0
95
0
Order By: Relevance
“…The requirement for mtHsp70 in granzyme mitochondrial import is less surprising as GA and GB have been shown to interact strongly with cytosolic Hsp27, Hsp70 and Hsp90. [69][70][71] SSC1-3 allele presents a G56S mutation in the mtHsp70 ATPase domain, 72 indicating that GB might cross the inner mitochondrial membrane in a forceful manner. Moreover SSC1-2 yeast strain carries an allele of mtHsp70 that poorly interact with Tim44 at 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement for mtHsp70 in granzyme mitochondrial import is less surprising as GA and GB have been shown to interact strongly with cytosolic Hsp27, Hsp70 and Hsp90. [69][70][71] SSC1-3 allele presents a G56S mutation in the mtHsp70 ATPase domain, 72 indicating that GB might cross the inner mitochondrial membrane in a forceful manner. Moreover SSC1-2 yeast strain carries an allele of mtHsp70 that poorly interact with Tim44 at 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…93 A large body of evidence implicates heat-shock protein 70 (HSP70) as a potential danger signal and it is interesting to note that HSP70 has been shown to mediate the uptake of granzyme B in a perforin-independent manner. 94 It is therefore intriguing to speculate that high levels circulating HSP70, released during situations of nonphysiological cell death such as chronic viral infection, may mediate the uptake of serum granzyme B by cells of the immune system and thus propagate the emerging proinflammatory properties of this protease. However, it is clear that investigations into the uptake of granzymes in noncytotoxic scenarios will require many more studies before a clearer picture begins to emerge.…”
Section: How Are Granzymes Released During Inflammation?mentioning
confidence: 99%
“…While it has been widely established that TLRs are the key mediators in the response to invading pathogens, there is a growing line of evidence suggesting that TLRs can be activated by endogenous "danger signals" released from the injured or necrotic cells. More particularly, TLR2 and TLR4 can interact with endogenous alarm signals such as heat shock proteins (Hsp60 and 70), extracellular breakdown product of hyaluron lipoproteins, etc., suggesting that TLRs may be involved in the regulation of inXammatory response following brain injuries [5,47,106] and neurodegeneration [99,105]. Recent studies demonstrated that TLRs, in particular TLR2 may be an important mediator of CNS ischemic injury [83,147].…”
Section: Tlrs Response To Ischemic Injury and Neurogenesismentioning
confidence: 99%